Alien Gene Transfer in Crop Plants, Volume 2 2013
DOI: 10.1007/978-1-4614-9572-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Lentil

Abstract: Lentil ( Lens culinaris Medik subsp. Culinaris ) is an important cool season food legume grown over a large area in the Indian subcontinent, west Asia, some parts of Africa and southern Europe. Keeping in view its great demand for nutritious seeds, efforts are underway in different research institutes for development of improved plant types with high yielding ability, disease and insect pest resistance, and seed weight. Improvement of grain quality and nutrition are also among the import breeding objectives. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…orientalis ( Gupta and Sharma, 2006 ). Earlier reports have indicated L. ervoides as a good source of alleles for plant architectural traits such as phenology, plant growth habit, and biomass besides seed traits ( Tullu et al, 2011 , 2013 ; Kumar et al, 2014 ). Based on the extensive evaluation of global wild Lens taxa representing 27 countries, Kumar et al (2014) observed wide variation for yield attributing traits, as well as resistance to multiple diseases in L. nigricans and L. ervoides .…”
Section: Potential Wild Species For Alien Gene Transfer Of Target Tramentioning
confidence: 99%
See 2 more Smart Citations
“…orientalis ( Gupta and Sharma, 2006 ). Earlier reports have indicated L. ervoides as a good source of alleles for plant architectural traits such as phenology, plant growth habit, and biomass besides seed traits ( Tullu et al, 2011 , 2013 ; Kumar et al, 2014 ). Based on the extensive evaluation of global wild Lens taxa representing 27 countries, Kumar et al (2014) observed wide variation for yield attributing traits, as well as resistance to multiple diseases in L. nigricans and L. ervoides .…”
Section: Potential Wild Species For Alien Gene Transfer Of Target Tramentioning
confidence: 99%
“…Earlier reports have indicated L. ervoides as a good source of alleles for plant architectural traits such as phenology, plant growth habit, and biomass besides seed traits ( Tullu et al, 2011 , 2013 ; Kumar et al, 2014 ). Based on the extensive evaluation of global wild Lens taxa representing 27 countries, Kumar et al (2014) observed wide variation for yield attributing traits, as well as resistance to multiple diseases in L. nigricans and L. ervoides . Nutritional quality traits in wild Lens showed significant diversity not only for micronutrients ( Sen Gupta et al, 2016 ; Kumar et al, 2018 ) but also for prebiotics, RFO, raffinose, and verbascose ( Tahir et al, 2011 ).…”
Section: Potential Wild Species For Alien Gene Transfer Of Target Tramentioning
confidence: 99%
See 1 more Smart Citation
“…Balance assembly lines are used generally to improve the assembly process for serial work stations. Assembly line balancing is a technique that is often used by industries that want to implement lean manufacturing systems (Kumar and Mahto, 2013). Measures of efficiency (operational performance) of assembly lines can be measured based on (Damayanti and Toha, 2012): 1.…”
Section: Assembly Line Balancingmentioning
confidence: 99%
“…Cars manufactured by XYZ Corp has several types of car products such as model A, model B, and model C. The flow of the car assembly process at XYZ Corp is a trimming line and a mechanical line. While the engine, door, tire, and dashboard subassembly process is an assembly sub-process on the assembly line in the production department, according to Kumar and Mahto (2013) the assembly line model at XYZ Corp has the characteristics of a mixed-model assembly line because the company produces several types of products on 1 track and there is no setup time for changes in the types of products assembled.…”
Section: Introductionmentioning
confidence: 99%